The Influence of Women’s Empowerment, Mental, and SpiritualDevelopment on New Entrepreneur Formation in PDA Kudus - Nurani Puspa Ningrum; Tuti Nadhifah; Aly Akbar Taftazani (Jurnal Ragam Pengabdian, 2026)
Women’s entrepreneurship plays an important role in strengthening household economic resilience and promoting inclusive economic development. However, many women still face challenges such as limited access to resources, insufficient entrepreneurial skills, and lack of institutional support. This study aims to analyze the influence of women’s empowerment, mental development, and spiritual development on the formation of new entrepreneurs within the Regional Leadership of Aisyiyah (Pimpinan Daerah Aisyiyah/PDA) Kudus through the Aisyiyah Entrepreneurship School (Sekolah Wirausaha Aisyiyah/SWA) program. This research employed a quantitative approach using multiple linear regression analysis. The data were collected from 40 respondents who participated in the entrepreneurship program, and the analysis was conducted using SPSS version 25. The results indicate that women’s empowerment and spiritual development have a significant positive effect on the formation of new entrepreneurs, while mental development does not show a significant effect in this study. Simultaneously, the three independent variables significantly influence the formation of new entrepreneurs with a coefficient of determination (R²) of 0.377, indicating that 37.7% of entrepreneurial formation can be explained by these variables, while the remaining variation is influenced by other factors outside the model. The findings also reveal that the Aisyiyah Entrepreneurship School plays a strategic role in empowering women through entrepreneurship training, strengthening business networks, and integrating spiritual values into entrepreneurial practices. These results suggest that community-based entrepreneurship programs that integrate economic empowerment and spiritual values can effectively encourage women to engage in entrepreneurial activities and contribute to local economic development